Aspects of faith in the Eunomian controversy - Vaggione, R (1976)
Despite the intense controversy which surrounded the Eunomian movement at its inception, and the continuing, if sporadic, attention. paid it in subsequent centuries, the theology of Eunomius has been relatively neglected. In particular, scholars have concentrated. almost entirely on Eunomius' Triniterian doctrine, and have paid little attention to other aspects of his system. This thesis is an attempt to remedy this neglect. In it we will explore the meaning and function of the various aspects of faith in Eunomian teaching. Particularly, we will try to ascertain its relationship to Eunomius' extensive use of rational argument, and his claim to apprehend the essence of God completely. It is hoped that we will thereby come to a better understanding of the functioning of Eunomianism as a religious system. Among the reasons why scholars have neglected Eunomius has been the small amount of available evidence, and the unreliable state of what little there is. Much of this thesis, therefore, is concerned with clarifying this evidence. Two parts of this thesis, deal with this problem: Part I and the various appendices. The latter include a critical text of the 'Liber Apologeticus' and the 'Esposito Fidei'. Part I concerns itself with each of surviving Eunomian works in turn and with some fragmentary material. It attempts to determine the provenance, authenticity, and reliability of each. The appendices deal with other aspects of the same problem. The second part of the thesis, Part II, deals with the problem of faith itself. In its opening section (by far the longest) it examines the evidence which has been alleged to show that in Eunomius' practice (if not his teaching) faith was completely dominated by reason. After a detailed analysis we are unable to substantiate this allegation, and are forced to the conclusion that the reason for it is as much. to be sought in the presuppositions of its authors as in the state of the evidence. The second section attempts to present another solution to this problem, one which looks at it with fresh eyes and from within. Particularly, we examine the Eunomian theory of language and its connection with the problem of revelation,, and; to the knowledge of God. In the end, we are able to conclude that so far from dominating revelation it is a guarantee of it, and provides us with a surety that a genuine knowledge of God is possible. It is in this context that the soul's ascent to God in faithful contemplation is to be understood. It is to be hoped that in reaching this conclusion, we have helped to clarify in some degree our understanding of this much-neglected, but very interesting ancient theologian.